Muslim Women Representation in Hijab Shampoo Advertisements - Meisa Alifia Utami (Passage, 2019)
This study entitled Muslim Women Representation in Hijab Shampoo Advertisements aims to reveal the representation of Muslim women in hijab shampoo advertisements focuses on the visual elements. The data are on the form of ten hijab shampoo advertisements, namely Wardah, Rejoice, Sunsilk, Emeron, Safi, Sariayu, Dove, Clear, Pantene and Lifebuoy which are taken from the website of each advertisement. The study applies a descriptive qualitative method and used a theory of three orders of signification proposed by Barthes (1987) to analyse the representation of Muslim women in the advertisements. The result of this research shows that Muslim women in hijab shampoo advertisements is represented as pure, beautiful, healthy, and modern. The representation constructed in the hijab shampoo advertisements is influenced by the use of fashion and its color, physical appearances, camera angle, and frame size. Keywords: Advertisement, Muslim women, Hijab, Shampoo.